2017
DOI: 10.1002/jso.24817
|View full text |Cite
|
Sign up to set email alerts
|

Management of primary malignant bone and soft tissue tumors of foot and ankle: Is it worth salvaging?

Abstract: LSS performed in specialized centers is an effective treatment method for malignant tumors of the foot and ankle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Previous reports in the literature are lacking meaningful prognostic information due to limited small sample sizes of malignant bone tumors. 1,2,9,12,14,[17][18][19][20]31 Univariate analysis in the current study showed older age, poor or undifferentiated grade, distant stage, size ≥8 cm, histology other than chondrosarcoma, surgical treatment other than local excision, and an earlier decade of diagnosis were found to be associated with poor outcomes. Of these, younger age group and localized stage, were found to be independent predictors of improved outcomes.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…Previous reports in the literature are lacking meaningful prognostic information due to limited small sample sizes of malignant bone tumors. 1,2,9,12,14,[17][18][19][20]31 Univariate analysis in the current study showed older age, poor or undifferentiated grade, distant stage, size ≥8 cm, histology other than chondrosarcoma, surgical treatment other than local excision, and an earlier decade of diagnosis were found to be associated with poor outcomes. Of these, younger age group and localized stage, were found to be independent predictors of improved outcomes.…”
Section: Resultsmentioning
confidence: 50%
“…To date, epidemiological and clinical reports describing foot neoplasms have emanated from single‐centers with limited number of patients 8,9 . Some studies have lumped benign and malignant tumors together while others have limited their analysis to a particular histopathological subtype 1,3,4,10–21 . Information regarding patient characteristics and prognostic factors is limited due to small patient sample sizes, heterogenous data, and single‐center studies that are susceptible to selection bias.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Many very distal extremity sarcoma series treated with limb sparing approaches report excellent MSTS scores. 14,[30][31][32][33] TESS measures physical disability and performance in activities of daily living, and is completed by the patient. 15 Though not specifically developed for extremity sarcomas, the disabilities of the arm, shoulder, and hand (DASH) questionnaire has also been utilized to evaluate patient-reported outcomes in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument, however, is completed by a physician 29 . Many very distal extremity sarcoma series treated with limb sparing approaches report excellent MSTS scores 14,30–33 . TESS measures physical disability and performance in activities of daily living, and is completed by the patient 15 .…”
Section: Discussionmentioning
confidence: 99%